2022
DOI: 10.1002/prep.202200012
|View full text |Cite
|
Sign up to set email alerts
|

On the Promotion of TKX‐50 Thermal Activity with Aluminum

Abstract: It is significant to investigate the effect of aluminum (Al) on the thermal activity of Dihydroxylammonium 5, 5'-bistetrazole-1, 1'-diolate (TKX-50) for the application of TKX-50-based composite solid propellant. In this work, TKX-50/Al composites with different particle sizes and contents of Al were blended, and the thermal decomposition and combustion properties were investigated by differential scanning calorimetry (DSC), thermal decomposition kinetic methods, laser ignition experiments, and constant-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Research found that the introduction of metal in the thermal decomposition process of TKX-50 can improve its thermal decomposition performance. Ju et al studied the decomposition process of the TKX-50 molecule on the surface of Al (111) by using the DFT method, to explore the decomposition mechanism of the pyrolysis of TKX-50 by Al. The activation energy of TKX-50/Al is lower than that of TKX-50 due to the formation of N–Al, O–Al, and OH–Al bonds on the surface of Al.…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
See 2 more Smart Citations
“…Research found that the introduction of metal in the thermal decomposition process of TKX-50 can improve its thermal decomposition performance. Ju et al studied the decomposition process of the TKX-50 molecule on the surface of Al (111) by using the DFT method, to explore the decomposition mechanism of the pyrolysis of TKX-50 by Al. The activation energy of TKX-50/Al is lower than that of TKX-50 due to the formation of N–Al, O–Al, and OH–Al bonds on the surface of Al.…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
“…It can be considered that aluminum atoms promote the fracture of the tetrazole ring of TKX-50 and accelerate the thermal decomposition process. Based on this simulation study, Guo et al carried out corresponding experiments on the pyrolysis process of TKX-50 catalyzed by Al. The thermal decomposition process of TKX-50/Al composites with different aluminum particle size and content was investigated by thermal analysis.…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum particles are utilized in a wide variety of industrial and military applications, such as nanocomposites, surface coatings, and explosives. For instance, in metal–matrix composites, understanding the wetting behavior is critical for manufacturing and processing composites. Since carbon is a common material to be used as reinforcement in composites, many studies have been performed on the aluminum–carbon system to understand its wetting behavior. However, most research studies focused on contact angle measurement via the sessile drop method under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion is a form of reaction with a faster rate of energy release than thermal decomposition [21][22][23]. The thermal analysis and combustion behaviors of new polynitrogen compounds is of great significance for the qualitative description of their reaction laws in the combustion process, the establishment of mathematical models, the calculation of kinetic parameters, thermodynamic parameters, and the development and application of new polynitrogen compounds [24][25][26][27].…”
mentioning
confidence: 99%